[5/4]^-x/[5/4]^-4 = [5/4]^5
bkrathi467:
[5/6]-x/[5/4]^-4=[5/4]^5
Answers
Answered by
19
Answer:
-9
Step-by-step explanation:
[5/4]^-x/[5/4]^-4 = [5/4]^5
[5/4]^ (-x-4) = [5/4]^5
base are same
-x -4 = 5
-x = 5 +4
-x = 9
x = - 9
hope this helped u !
please vote
Answered by
4
Answer:
-9
Step-by-step explanation:
[5/4]^-x/[5/4]^-4 = [5/4]^5
[5/4]^ (-x-4) = [5/4]^5
base are same
-x -4 = 5
-x = 5 +4
-x = 9
x = - 9
Similar questions
Social Sciences,
7 months ago
Math,
7 months ago
Computer Science,
1 year ago
Chemistry,
1 year ago
Math,
1 year ago